A study on the “excessive” emergency behavior of local governments in the context of the covid-19 epidemic – Based on the perspective of phenomenological sociology - Shen Yang (SHS Web of Conferences, 2023)
The “excessive” emergency behavior of local governments at all levels in China has caused adverse social impacts during the covid-19 epidemic prevention and control period. From the perspective of phenomenological sociology, this paper uses the method of case study to analyze the motivation of “excessive” emergency behavior in the process of local government epidemic prevention, and understand the “real cause motivation” and “purpose motivation” behind such behaviors. The study found that the “excessive” emergency behavior of local governments is more caused by irrational factors from personal, social risks and local fiscal capacity.